Reminiscence in dementia: A concept analysis. (March 2014) - Dempsey, Laura; Murphy, Kathy; Cooney, Adeline; Casey, Dympna; O'Shea, Eamon; Devane, Declan; Jordan, Fionnuala; Hunter, Andrew
This paper is a report of an analysis of the concept of reminiscence in dementia and highlights its uses as a therapeutic intervention used on individuals with dementia. No single definition of reminiscence exists in healthcare literature; however, definitions offered have similar components. The term life review is commonly used when discussing reminiscence; however, both terms are quite different in their goals, theory base and content. This concept analysis identified reminiscence as a process which occurs in stages, involving the recalling of early life events and interaction between individuals. The antecedents of reminiscence are age, life transitions, attention span, ability to recall, ability to vocalise and stressful situations. Reminiscence can lead to positive mental health, enhanced self esteem and improved communication skills. It also facilitates preparation for death, increases interaction between people, prepares for the future and evaluates a past life. Reminiscence therapy is used extensively in dementia care and evidence shows when used effectively it helps individuals retain a sense of self worth, identity and individuality.